Developing a national financial education strategy towards the goal of inclusive and sustainable financial development: International experience and implications for Vietnam - Khanh, Tran Nam (West Science Accounting and Finance, 2024)
This study was conducted to examine the important role of financial education in promoting financial inclusion and sustainable development. By analyzing experiences from successful countries such as Australia, Canada, and the United Kingdom. At the same time, based on the results of semi-structured interviews with 15 subjects, including policymakers, educators, financial service providers and other stakeholders to explore their experiences and perspectives on national financial education strategies towards inclusive and sustainable financial development. The results of the study identify valuable experiences for Vietnam such as effective government leadership, collaborative approaches, lifelong learning strategies, and targeted programs for vulnerable groups. Based on the results of the study, the proposed recommendations include establishing a centralized authority to coordinate activities, mobilizing resources through public-private partnerships, adopting community-based approaches, and developing curriculum appropriate to the context. By implementing the proposed recommendations, Viet Nam can improve the financial literacy and welfare of its people, promote financial inclusion, and contribute to the broader development goals.